Localized surface plasmon resonance (LSPR) based biosensors - Chen, Peng (2015)
Biosensors provide a quick and cheap alternative way of characterization and analysis as compared to standard analytical methods such as spectrometry, chromatography, biochemical or microbiological techniques. In the past few decades, biosensors have been quickly developed both in fundamental research and applications in the areas of medical diagnosis, pharmaceutics and environmental monitoring, as well as food, forensic, sports and defense and military science etc. Many different sensing platforms including the enzyme-linked immunosorbent assay (ELISA), surface plasmon resonance (SPR) and electrochemical sensor have been developed and found practical applications in medical diagnosis, environmental monitoring, detection of explosives etc.1,2 Most of these sophisticated sensing platforms are available at test centers, laboratories and hospitals etc. Moreover, these biosensors generally require professional training on operation. In this thesis, I developed some biosensor that is suitable for field test. These sensors are generally robust enough to stand for harsh environmental conditions, simple to operate and require minimal instrumentations. Localized surface plasmon resonance (LSPR) of gold nanoparticles has attracted tremendous interest in biosensing, due to its unique optical properties. The frequency and strength of the surface plasmon resonance of noble metal nanoparticles is affected by many factors, including the size, shape, inter-particle distance and surrounding medium etc. The resonance frequency and strength of the local electromagnetic field can be used to monitor the molecular interactions (bindings) occurs on (near) the surface of particle. In addition, graphene, a new 2D carbon material has been widely used in biosensing since its discovery in 2004, due to its excellent electrical and fluorescence quenching properties. The two materials are used as active materials for biosensors for their excellent property and chemical stability. A colorimetric sensor for MMP-7, a cancer marker was designed based on peptide functionalized gold nanoparticles (AuNPs). Presence of MMP-7 digests the peptide, leading to aggregation of the AuNPs. A colorimetric change of the solution from red to blue can be detected by the naked eye. This colorimetric sensor has a huge potential because it is easy for use and it does not require any instrumentation. Compared to SPR sensor, the refractive index (RIU) sensitivity of LSPR sensor is lower. I demonstrated that the sensitivity can be increased significantly by assembling simple spherical AuNPs into preferred configurations in 2D plane and 3D clusters. In addition to sensitivity, the noise level of LSPR peak is equally important. I demonstrate that by analyzing the LSPR peak using the curvature (overall shape of the peak) could improve the Signal-to-noise ratio for a few times than traditional methods based on peak shift and extinction. In addition, curvature is less affected by instrumental/chemical instabilities than peak shift and extinction. I also designed a hybrid sensing platform relying on two or more independent transducing mechanisms, LSPR and Raman scattering. A prototype platform for hybrid sensor was developed by assembling gold-silver alloy particles on graphene oxide. For biomolecules, it is generally difficult to observe the Raman scattering due to the low Raman scattering compared to the high fluorescence background. With this novel substrate, the Raman scattering is significantly enhanced, while fluorescence is quenched. The Raman to fluorescence ratio is improved by 6 orders of magnitude. In addition, this substrate can be used the same way as the LSPR sensor, where the LSPR peak shift, extinction and curvature can be used to monitor the molecule binding. With two independent responses on the same chip, more information can be obtained and the false responses from contaminants can be discriminated.